Maternal health status and household food security on determining childhood anemia in Bangladesh -a nationwide cross-sectional study - Masum Ali; Md. Ruhul Amin; Johan Jarl; Nick Chisholm; Sanjib Saha (BMC, 2021)
Abstract Background The aim of this study was to examine the effect of household food security on childhood anemia in Bangladesh while controlling for socioeconomic and demographic factors. Methods We used nationally representative Bangladesh Demographic Health Survey (BDHS) 2011 data for this study, the only existing survey including anemia information and household food security. The sample included 2171 children aged 6-59 months and their mothers. Differences between socioeconomic and demographic variables were analyzed using Chi-square test. Univariate and multivariate logistic regression analyses were performed to estimate the effects of different socioeconomic and demographic factors on childhood anemia. We also performed mediation analysis to examine the direct and indirect effect of household food security on childhood anemia. Results In Bangladesh, 53% male (95% CI: 50-56) and 51% female (95% CI: 47-54) children aged 6-59 months were anemic in 2011. The food insecure households have 1.20 times odds (95% CI: 0.97-1.48) of having anemic children comparing to food secure households in the unadjusted model. On the other hand, anemic mothers have 2 times odds (95% CI: 1.67-2.44) of having anemic children comparing to non-anemic mothers. However, household food security is no longer significantly associated with childhood anemia in the adjusted model while mothers' anemia remained a significant factor (OR 1.87: 95% CI: 1.53-2.29). Age of children is the highest associated factor, and the odds are 4.89 (95% CI: 3.21-7.45) for 6-12 months old children comparing to 49-59 months in the adjusted model. Stunting and household wealth are also a significant factor for childhood anemia. Although food security has no significant direct effect on childhood anemia, maternal anemia and childhood stunting mediated that relationship. Conclusions Future public health policies need to focus on improving mothers' health with focusing on household food security to eliminate childhood anemia.